Effect of inhalation application of lavender essential oil on slaughter and carcass characteristics and serum biochemistry in Texas quail - Arslan, Emre; Ayran Colak, Irem; Ozturk, Rahile; Bayar, Irem; Celik, Sadiye Ayse; Bayir, Tuba (Elsevier, 2025)
The aim of this study is to determine the effect of the lavender essential oil inhalation on slaughter and carcass characteristics and biochemical parameters of Texas quails. The material of the study consisted of 72 Texas quails aged between 28 and 42 days and the application was carried out in a 2x2 trial set-up. Inhalation application was carried out in the 4x4 m poultry breeding rooms in the Alternative Poultry Unit at the Prof. Dr. H & uuml;meyra Ozgen Research and Application Farm. Lavender essential oil, extracted by distillation, was applied to Texas quails at solution of 0.1 % concentration for 1 h per day for 14 days. A total of 12 quails, including 3 females and 3 males from each group, were slaughtered at the age of 42 days and their slaughter and carcass characteristics were determined. Serum biochemistry values were determined with blood samples taken from the quails during slaughter. As a result of the study, it was determined that the inhalation method did not affect the slaughter and carcass characteristics of 28-42 day-old Texas quails, but it had a reducing effect on HDL, triglyceride, and glucose values, which indicate lipid and carbohydrate metabolism, among the serum biochemistry values examined. Considering the positive effects of the inhalation of lavender essential oil on animal health, it is recommended to conduct more comprehensive studies.
Keywords: Lavender; Inhalation; Texas quail; Carcass; Metabolism